An introduction to data analysis using IBM SPSS - Jasrai, Lokesh (London Routledge, 2025)
This textbook elaborates on the basic understanding and application of statistical tests and data analysis using hypothetical datasets and SPSS version 22.0. It presents step-by-step processes and to-the-point interpretation for quick assimilation and comprehension. Data Analysis Using SPSS Begins with the stages of data entry and goes on till editing and data visualization.